NUMERICAL SIMULATION OF SHPB DYNAMIC COMPRESSION TEST OF CONCRETE - LI XiaoQin; CHEN BaoQi; DU Xi; DING ZuDe (Jixie qiangdu)
Split Hopkinson pressure bar（SHPB） tests are widely used for testing material mechanism behavior under high strain rates,A series of SHPB numerical tests were done based on K＆C local concrete damage model,The stress-strain curves of the concrete specimens were reconstructed with the two-wave theory,and the damage of the concrete was analyzed.According to the comparison between the numerical and the test results,Proving K＆C model can simulate concrete in concrete under high strain rate compressive mechanical behavior.Proving the increase of dynamic strength of concrete under the influence of structural effects.